Never give up? The persistence of welfare participation in Sweden - Thomas Andrén; Daniela Andrén (IZA Journal of European Labor Studies, 2013)
Long-term social assistance dependency is a growing concern in Sweden and other European countries. In order for policy makers to design effective welfare reforms it is important to know how strong the state dependence associated with social assistance is in the population and to what extent it varies with different factors, and among different groups. We estimate the effect of the state dependence in social assistance for Sweden during the 1990s, for both Swedish-born and foreign-born. Using a dynamic discrete choice model that controls for unobserved heterogeneity and the initial conditions problem, we found that the effect is three times larger for foreign-born compared to Swedish-born. However, when the effect is distributed over time, it decreases and loses significance after three years for both groups. This suggests that resources should be allocated for programs that connect working-age recipients with the labor market as early as possible.
Keywords: I30; I38; J18; 330; social assistance; welfare persistence; state dependence; unobserved heterogeneity; initial conditions problem; dynamic probit model; GHK simulator; Öffentliche Sozialleistungen; Dauer; Probit-Modell; Simulation; Schweden